Keberlanjutan Unesco Creative City Network di Kota Pekalongan (Analisis Aktor dan Hambatan Pada Kota Kreatif) - Jihan Amelia Syahidah (As-Shahifah : Journal of Constitutional Law and Governance, 2021)
The aim of this research is to explain how the sustainabiliy of UNESCO Creative City Network predicate for Pekalongan City based on the actors involved and success indicators for Pekalongan City in order to mention the barriers appeared that associated with the continuity of the UCCN This research used Qualitative approach and supported by simple Quantitative method by collecting data technique using depth interviews, observations, document studies and questionnaire with 100 respondents. The research result shows that the sustainability of creative city in Pekalongan are in the state of suspended animation and still being ruled out because there are other things to be considered more important by Pekalongan Government. Tools and infrastucture are not available such as there is no creative room and abandoned technopark construction. Besides, the integrity of actor has not been tied together well because the differences of opinion and mindset. Pekalongan Creative City Forum (PCCF) has not been able to take the role maximally so thereby appeared the barriers along with the sustainability of the UCCN. To do so requires efforts to give socializations and knowledge transfer to the society, in addition to create tools and infrastucture to support the creative city especially in building a place where involved actors can gather together.